ANALYSIS OF ADMINISTRATIVE PERSONNEL IN IMPROVING PUBLIC SERVICES AT THE BARU TANCUNG VILLAGE OFFICE, TANASITOLO DISTRICT, WAJO REGENCY - Baso Faried Yusra; Imran Ismail; Besse Herlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this study was to analyze administrative staff in improving public services in the Baru Tancung Village Office, Tanasitolo District, Wajo Regency and to analyze the factors that influence administrative staff in improving public services in the Baru Tancung Village Office, Tanasitolo District, Wajo Regency. The research method used is qualitative research with primary data sources totaling 5 people, namely 1 head of government section, 1 population administration staff, and 3 communities. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results of the Administrative Worker's research in improving public services in the Baru Tancung Village Office, Tanasitolo District, Wajo Regency, from the five public services are good, so that services can run effectively and efficiently. Factors that influence administrative staff in improving public services at the Baru Tancung Village Office, Tanasitolo District, Wajo Regency are divided into 2, namely supporting and inhibiting factors. Supporting factors for administrative personnel in public services are physical evidence such as infrastructure, equipment, chairs, tables, cabinets, benches, computers, printers, etc, reliability, responsiveness and good response, and empathy such as attention and courtesy. While the factors that hinder administrative staff in public services are work discipline that still needs to be improved.